2021
DOI: 10.1016/j.isci.2021.102493
|View full text |Cite
|
Sign up to set email alerts
|

Replication protein A plays multifaceted roles complementary to specialized helicases in processing G-quadruplex DNA

Abstract: RPA efficiently prevents G4 formation by preempting ssDNA before its folding Loop length may direct folded G4s to different unfolding way by RPA and helicases RPA promotes helicasemediated repetitive G4 unfolding into durative linear state RPA assists BLM to overcome G4 obstacle and continue to unwind downstream duplex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…Furthermore, as the stability of the qDNA structure increased, the fraction of unfolded molecules decreased only slightly in the case of antiparallel qDNA but was reduced significantly in the case of G-quadruplexes with a parallel conformation. Additional evidence was later obtained by another investigation employing smFRET to support the conclusion that antiparallel conformations of qDNA are unwound more efficiently . Furthermore, this study found qDNA structures with shorter loops were barely unfolded and reaffirmed the hypothesis that Pif1 is highly sensitive to the thermal stability of the qDNA.…”
Section: G-quadruplex Biology: Ally or Enemy To Genomic Maintenance?supporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, as the stability of the qDNA structure increased, the fraction of unfolded molecules decreased only slightly in the case of antiparallel qDNA but was reduced significantly in the case of G-quadruplexes with a parallel conformation. Additional evidence was later obtained by another investigation employing smFRET to support the conclusion that antiparallel conformations of qDNA are unwound more efficiently . Furthermore, this study found qDNA structures with shorter loops were barely unfolded and reaffirmed the hypothesis that Pif1 is highly sensitive to the thermal stability of the qDNA.…”
Section: G-quadruplex Biology: Ally or Enemy To Genomic Maintenance?supporting
confidence: 72%
“…Building upon these earlier investigations, a subsequent series of experiments performed using smFRET explored the effect of the length of the loops present in a qDNA molecule on its thermal stability. Surprisingly, it was also found that RPA quickly linearizes DNA before it can be folded into qDNA structures . In the majority of instances, the FRET efficiency of the linearized DNA did not increase despite being exposed to the correct conditions for qDNA folding.…”
Section: G-quadruplex Biology: Ally or Enemy To Genomic Maintenance?mentioning
confidence: 99%
“…Besides its ability to dissolve dHJ, BLM binds and unwinds G4 structures in vitro [61,102]. Sister chromatid exchange events (SCEs) are a byproduct of DSB or collapsed replication forks that are repaired via HR [117,118]. Strand-seq analysis revealed that SCEs are enriched at G4 motifs in BLM-deficient cells indicating that G4 structures can trigger SCE in the absence of BLM [64].…”
Section: Pathwaymentioning
confidence: 99%
“…However, their cooperation with helicases has not been well studied. Recently, Hou’s group used smFRET to study the relationship between RPA, PIF1, and BLM ( Wang et al, 2021 ). They found that both RPA and helicases were need for stable G4 DNA unfolding, and RPA played a complementary role for G4 unfolding by helicases ( Wang et al, 2021 ).…”
Section: Representative Research Methods To Reveal Molecular Mechanismsmentioning
confidence: 99%